Mapping non-state actors in international relations - Charountaki, Marianna; Irrera, Daniela (Cham : Springer, 2022)
This edited volume addresses the role of non-state actors (NSAs) in international relations. From their emergence in the early 20th century, entities of non-state status have played a role of increasing prominence in international politics. Scholarly work has been slow to catch up, approaching NSAs mainly through the scope of legitimacy and international law or limiting focus to NGOs, international organizations, and economic corporations. This volume remedies that, creating a typology of NSAs based on systematic and coherent analysis. Presenting a series of cases of NSAs across the continuum of international relations, the chapters firmly ground NSAs in the ontology of international relations theory. Filling a gap in the current literature, this book will be of interest to students and researchers of international relations theory, international politics, international security, diplomatic history, and European and Middle East politics, as well as policy-makers and practitioners
Chapter 1 - Conceptualising Non-State actors in International Relations -- Chapter 2 The power of institutions in IR: From intergovernmental to non-governmental organizations -- Chapter 3 - Irregular Militaries and Militias in International Relations Theory: The Case of Iraqi Shiite militias -- Chapter 4 - Dilemmas of fundamentalist non-state actors in international relations -- Chapter 5 - The impact of ethnic groups on International Relations -- Chapter 6 - States-to-Be as Foreign Policy Actors -- Chapter 7 - Conclusion. Understanding the role of non-state actors in a mutable global system
Includes index
Keywords: Non-state actors (International relations)